Accuracy of single quantum dot registration using cryogenic laser photolithography - Lee, K; Green, A; Taylor, R; Waldermann, F; Sena, A; Sharp, D; Turberfield, A; Brossard, F; Williams, D (2006)
We have registered the position of single InGaAs quantum dots using a novel cryogenic laser photolithography technique. This would be useful in realizing solid state cavity quantum electrodynamics. By fabricating metal alignment markers around the quantum dot, it was registered with an accuracy of 50 nm. Following the marker fabrication process we demonstrated that the same quantum dot was reacquired, with an accuracy of 150 nm. The photoluminescence spectra from the quantum dots before and after processing were identical except for a small red shift (∼1 nm), probably introduced during the reactive ion etching. © 2006 IEEE.